Representation Of Family Financial Communication Patterns In The Film HOME SWEET LOAN - Astrid Nabillah; Yani Achdiani; Sarah Nurul Fatimah (Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the representation of financial communication patterns in families as shown in the film Home Sweet Loan. The approach used in this study is a qualitative method with content analysis techniques to examine dialogue, character interactions, and the dynamics of financial conflicts that occur in the film. The results of the study indicate that openness in financial communication plays an important role in maintaining household economic balance, while lack of transparency can trigger conflict and financial instability. The film Home Sweet Loan also illustrates how healthy communication patterns can help families in preparing budgets, managing debt, and increasing family members' awareness of the importance of financial planning. The interpretation of the film Home Sweet Loan not only represents the social reality of financial management in families, but also illustrates the importance of open communication in building economic stability and household harmony.